2015
DOI: 10.1016/j.joen.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fracture Sites and Post Lengths in Longitudinal Root Fractures

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
6
19
0
5
Order By: Relevance
“…The findings from this study showed that female patients had 2 times higher odds for the clinical presentation of VRFs within 5 years postoperatively. This increased propensity of VRFs in females is in agreement with previous findings (12,19). Conversely, Chan et al (21) reported that males have 1.4 times more VRFs than females in endodontically treated teeth.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings from this study showed that female patients had 2 times higher odds for the clinical presentation of VRFs within 5 years postoperatively. This increased propensity of VRFs in females is in agreement with previous findings (12,19). Conversely, Chan et al (21) reported that males have 1.4 times more VRFs than females in endodontically treated teeth.…”
Section: Discussionsupporting
confidence: 91%
“…Various studies have evaluated the clinically relevant factors (12,16,19) and radiographic features associated with VRFs (20). Some studies have included both endodontically treated as well as nonendodontically treated teeth in their analysis (12,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) The VRF load is proportional to dentin fracture toughness K C . Hence, VRF should be more common in older patients, for which K C is known to reduce with age [67,68], consistent with clinical trends [8,69,70]. Bacteria-accommodating dentinal cracks [71] is another important cause for reducing K C (see also Chap.…”
Section: Conclusion and Observationssupporting
confidence: 52%
“…The site of fracture was classified into buccal and/or lingual, mesial and/or distal, and other (fracture affecting both buccal/lingual and mesial/distal sites). The fracture regions in longitudinal axial direction were classified into complete fractures or incomplete fractures, and incomplete fractures were further classified into the three subgroups of cervical region fracture, mid-region fracture, and apical region fracture [12].…”
Section: Introductionmentioning
confidence: 99%